2005
DOI: 10.1111/j.1745-4530.2005.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transport in a Multiple Jet Impingement Oven

Abstract: Three-dimensional numerical simulation of flow field and heat transfer in a jet impingement oven with multiple jets was carried out. Distribution of local heat transfer coefficient on a model cookie in the oven cavity was obtained from the predicted flow and temperature fields, and compared with the experimentally measured values. Effects of air temperature (400, 450K) and air velocity (2.5, 5, 10 m/s), on the surface heat transfer coefficient were studied. Numerical predictions showed good agreement with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…When the ventilation level was reduced, h c fell from 38 to 26 W m À2 K À1 , thus showing strong dependence on convection rather than temperature. These results are in agreement with those of Kocer and Karwe (2005), who found average values of 24-42 W m À2 K À1 in a jet impingement oven with air velocities ranging from 2.5 to 10 m/s for air temperatures ranging from 127-177°C. The relative contribution of radiative flux to total surface heat flux ranged from 22% to 42% for the tested temperature settings at maximum ventilation; it was substantially the same whatever the ventilation level.…”
Section: Settings (°C)supporting
confidence: 94%
“…When the ventilation level was reduced, h c fell from 38 to 26 W m À2 K À1 , thus showing strong dependence on convection rather than temperature. These results are in agreement with those of Kocer and Karwe (2005), who found average values of 24-42 W m À2 K À1 in a jet impingement oven with air velocities ranging from 2.5 to 10 m/s for air temperatures ranging from 127-177°C. The relative contribution of radiative flux to total surface heat flux ranged from 22% to 42% for the tested temperature settings at maximum ventilation; it was substantially the same whatever the ventilation level.…”
Section: Settings (°C)supporting
confidence: 94%
“…The governing equations for turbulent fluid flow, heat transfer and conduction heat transfer within a solid object are not given here for brevity. They have been described in many textbooks and papers (most recently by Kocer and Karwe 2005). The standard k‐ ε model (Arpaci and Larsen 1984; Jaluria and Torrance 1986) was used to simulate turbulence.…”
Section: Methodsmentioning
confidence: 99%
“…The lumped mass approach (Nitin and Karwe 2001; Kocer and Karwe 2005) was used to determine the average surface heat transfer coefficient ( h ). This approach is valid when the value of Biot number Bi (= h R/ k s ) is less than 0.1, where R is the radius of the cylinder and k s is the thermal conductivity of this solid.…”
Section: Methodsmentioning
confidence: 99%
“…As well, Xue and Walker (2003) recently reported values up to 72.2 W/m 2 K for baking using an electrically heated air jet impingement oven, with the air velocity reaching about 9 m/s. Average values of 24-42 W/m 2 K were reported as heat transfer coefficients by Kocer and Karwe (2005) in a numerical simulation analysis validated with experimental data using a commercial jet impingement oven with air velocities ranging from 2.5 to 10 m/s and air temperatures ranging from 400 to 450 K (127-177°C). Those authors concluded that the h value was strongly a function of the air velocity but not the air temperature.…”
Section: Convection Heat Transfer Coefficientmentioning
confidence: 99%
“…Thermodor developed the JetDirect oven using the Enersyst technology for domestic applications in order to cook starchy products in a fraction of the conventional baking time (Norris, Abbott, & Dobie, 2002). Kocer and Karwe (2005) reported average heat transfer coefficient values of 24-42 W/m 2 K using a Fujimak multiple jet impingement oven, and found that these values were strongly a function of air velocity ranging from 2 to 10 m/s.…”
Section: Introductionmentioning
confidence: 96%